SEISMIC AND WIND RISK EVALUATION OF REINFORCED CONCRETE TALL PIER BRIDGES LOCATED IN MOUNTAIN REGIONS - Aayush Aggarwal,; Swati Chaudhary, (IJRDO - Journal of Mechanical And Civil Engineering, 2025)
The bridges built in the mountainous areas experience a combination of structural requirements because of the rocky terrain, high seismicity, and wind acceleration. This paper gives an account of an in-depth evaluation of a tall hollow circular reinforced concrete pier, 52.8 meters tall, supporting a highway bridge at the approach to the Khellani Tunnel in the Jammu and Kashmir region, which falls under the highest seismic risk category in India. The Indian Road Congress (IRC) design standards considered structural behavior under seismic and wind loading conditions using the numerical simulation tools, i.e., Structural Analysis and Design Program (STAAD Pro) and Midas Civil. It was found that the forces due to the wind, especially in the transverse direction, were greater than the seismic forces, and the highest wind force was recorded as 765.7 kilonewtons. This brings out wind as the controlling element in structural design in this case. The circular shape of the pier was hollow, which was determined to increase the performance due to the less mass of the structure, better lateral flexibility, and the ease of ductility. The building was able to achieve strength-based performance and serviceability-based performance requirements, and this shows that the design was compliant and resilient. The findings advocate for the wider adoption of hollow reinforced concrete piers in similar high-altitude, wind-sensitive regions. They also emphasize the importance of integrating wind considerations into seismic-resistant bridge design to ensure safety, economy, and long-term performance.